Catholic Education at Schools of Sisters Servants of Mary Immaculate in Mariówka in the Years 1903-1954 - Grażyna Wójcik (Nicolaus Copernicus University in Toruń, 2018)
The article presents the functioning of the schools run by Sisters Servants of Mary Immaculate in Mariówka at the background of the education development in Poland in the years 1903-1954. What is considered is the situation of the Catholic Church that approached then the matters of youth education with utmost care. At that time there were many religious congregations developing their own pedagogies and educational methods. In 1903 Sisters Servants of Mary Immaculate began an original educational program and since then they have worked out their own system of dealing with the youth which has guaranteed a Catholic education to pupils.